Tailoring nanohole sizes through the deacetylation process in chitosan powders obtained from squid pens - Lucanera, Eliana Soledad (2022)
An experimental study on the evolution of the physicochemical, thermal and nanostructural properties of chitosan samples obtained from squid pens as the deacetylation treatment proceeds is presented. To this aim, potentiometric titration, capillary viscosimetry, infrared spectroscopy, differential scanning calorimetry and positron annihilation lifetime spectroscopy were used. The results obtained are discussed in terms of the influence of the deacetylation time on the deacetylation degree, average molecular weight, thermal parameters and average free nanohole size of the different samples. A way of preparing chitosan matrices with tailored nanostructural characteristics for specific applications through the deacetylation process is explored.